Détour par Calcutta . Detour Calcutta - Rossier, François (Belle Journée Productions, 2004)
Duration: 00:50:00 One day, the director meets a friend of the mayor of Calcutta who asks him: "You're a film maker, aren't you? Why don't you make a film about our mayor?!" That is how the film was born. Originally planned as a simple portrait of Calcutta's mayor, it gradually becomes - through various difficulties met on location (bureaucracy, the director's preconceived ideas, heat) - an essay on tinkering about, and chaos, and a reflection on the documentary genre. In this shooting diary, the director speaks in first person voiceover, without trying to hide what's off camera. On the contrary: that's where he points his lens, looking for a good subject, because his main character - the mayor - disappears after the first third of the shoot. We are taken through an Indian sub-continent metropolis of 17 million inhabitants, led by astonishing chances which the director - a little Swiss - reorganizes in his own style, so that his beautiful escape becomes ours too.